Fifty top-cited spine articles from mainland China: A citation analysis. Issue 2 (February 2018) - Wu, Yaohong; Zhao, Yachao; Lin, Linghan; Lu, Zhijun; Guo, Zhaoyang; Li, Xiaoming; Chen, Rongchun; Ma, Huasong
Objective: To identify the 50 top-cited spine articles from mainland China and to analyze their main characteristics. Methods: Web of Science was used to identify the 50 top-cited spine articles from mainland China in 27 spine-related journals. The title, year of publication, number of citations, journal, anatomic focus, subspecialty, evidence level, city, institution and author were recorded. Results: The top 50 articles had 29–122 citations and were published in 11 English-language journals; most (32) were published in the 2000s. The journal Spine had the largest number of articles and The Lancet had the highest impact factor. The lumber spine was the most discussed anatomic area (18). Degenerative spine disease was the most common subspecialty topic (22). Most articles were clinical studies (29); the others were basic research (21). Level IV was the most common evidence level (17). Conclusions: This list indicates the most influential articles from mainland China in the global spine research community. Identification of these articles provides insights into the trends in spine care in mainland China and the historical contributions of researchers from mainland China to the international spine research field.